2016
DOI: 10.1111/ijfs.13082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different freeze drying cycle in Semimembranous and Gluteus Medius bovine muscles: changes on microstructure, colour, texture and physicochemical parameters

Abstract: The aim of the present research was to evaluate effects of freeze drying cycle in Semimembranous and Gluteus Medius bovine muscles (sp: Aberdeen Angus) for instant meal. Samples were analysed by Scanning electron microscopy; texture and colour parameters were analysed by image analysis and physicochemical properties by instrumental assays. Micrographs revealed that a higher porous size structure and shrinkage of muscle fibre diameter were obtained at À40°C. In Semimembranous and Gluteus Medius bovine muscles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…However, yellowness (b* value) is more influenced by lyophilization time and pressure than the other two variables: freezing temperature and lyophilization time. These results differ from those reported in other studies that reported that color parameters are affected by freezing and drying time [46].…”
Section: Color Difference Of Dried Mexican Kefir Grainscontrasting
confidence: 99%
“…However, yellowness (b* value) is more influenced by lyophilization time and pressure than the other two variables: freezing temperature and lyophilization time. These results differ from those reported in other studies that reported that color parameters are affected by freezing and drying time [46].…”
Section: Color Difference Of Dried Mexican Kefir Grainscontrasting
confidence: 99%